Evolutionary plasticity and functional repurposing of the essential metabolic enzyme MoeA - Daniela Megrian; Mariano Martinez; Pedro M. Alzari; Anne Marie Wehenkel (Communications Biology)
Abstract MoeA, also known as gephyrin in higher eukaryotes, is an enzyme essential for molybdenum cofactor (Moco) biosynthesis and involved in GABA and GlyR receptor clustering at the synapse in animals. We recently discovered that Actinobacteria have a repurposed version of MoeA (Glp) linked to bacterial cell division. Since MoeA exists in all domains of life, our study explores how it gained multifunctionality over time. We use phylogenetic inference and protein structure analyses to study its diversity and evolutionary history. Glp-expressing Bacteria have at least two copies of the gene, and analysis of their putative active sites suggests that Glp lost its enzymatic role. In Archaea, we find an ancestral duplication, with one paralog that may bind tungsten instead of molybdenum. Early eukaryotes acquired MoeA from Bacteria, MogA fused with MoeA in the opisthokont ancestors, and it finally gained roles in anchoring inhibitory neurotransmitters. Our findings highlight MoeA’s functional versatility and repurposing.